Vascular dysfunction in retinitis pigmentosa. Issue 7 (17th May 2019) - Lang, Matt; Harris, Alon; Ciulla, Thomas A.; Siesky, Brent; Patel, Pooja; Belamkar, Aditya; Mathew, Sunu; Verticchio Vercellin, Alice C.
Abstract: The relationship between ocular haemodynamics and retinitis pigmentosa (RP) has not been fully understood. Reductions in blood flow have been established in RP patients by a variety of studies; however, questions have yet to be answered regarding the role of vascular dysfunction in photoreceptors (PR) degeneration, the causes of vascular dysfunction in RP, as well as the diagnostic, prognostic and perhaps therapeutic potential of measuring ocular haemodynamics in RP patients. While significant evidence supports the theory that vascular dysfunction is associated with but not the cause of PR death in retinitis pigmentosa, evidence suggests that vascular abnormalities in the foveal and parafoveal regions may exacerbate cone cell loss. Additional evidence demonstrates that vascular dysfunction likely results from changes in metabolic demand due to death of PR cells in the retina. Detection and monitoring of ocular blood flow, retinal oxygen saturation, endothelin‐1 levels and vascular structural abnormalities could provide diagnostic, prognostic and therapeutic potential for patients with RP.